2022
DOI: 10.3390/ijerph191610230
|View full text |Cite
|
Sign up to set email alerts
|

Revealing Impacts of Human Activities and Natural Factors on Dynamic Changes of Relationships among Ecosystem Services: A Case Study in the Huang-Huai-Hai Plain, China

Abstract: Understanding the dynamic changes of relationships between ecosystem services (ESs) and their dominant factors can effectively adjust human activities to adapt proactively to global climate change. In this study, the Huang-Huai-Hai Plain (HHHP) was selected to assess the dynamics of four key ESs (NPP, net primary productivity; WY, water yield; SC, soil conservation; FP, food production) from 2000 to 2020. The constraint lines of interactions among ESs were extracted based on a segmented quantile regression mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 60 publications
0
1
0
Order By: Relevance
“…Between 2000 and 2020, there was a noticeable increase in land occupied by built-up areas, rising from 13.14 to 18.13%, consequently exerting mounting pressure on the ecological environment. The conflict between promoting regional socio-economic development and ensuring ecological environmental conservation has emerged as a significant constraint on the HHHP's sustainable development, leading to adverse consequences for the local community welfare (Deng et al 2022b).…”
Section: Study Areamentioning
confidence: 99%
See 3 more Smart Citations
“…Between 2000 and 2020, there was a noticeable increase in land occupied by built-up areas, rising from 13.14 to 18.13%, consequently exerting mounting pressure on the ecological environment. The conflict between promoting regional socio-economic development and ensuring ecological environmental conservation has emerged as a significant constraint on the HHHP's sustainable development, leading to adverse consequences for the local community welfare (Deng et al 2022b).…”
Section: Study Areamentioning
confidence: 99%
“…Considering the natural characteristics and socioeconomic conditions of the HHHP, and drawing from prior studies (Deng et al 2022b), this study identified several potential driving factors (refer to Table 2) and utilized the ALM model (Zhang et al 2021a) to analyze the primary factors influencing the ES trade-offs. Through the removal of irrelevant variables and the management of multicollinearity among factors, the ALM model produced optimal regression outcomes.…”
Section: Automatic Linear Modelling (Alm)mentioning
confidence: 99%
See 2 more Smart Citations
“…For identification of attributes related to water yield capacity, common methods include scenario analysis (Yang J. et al, 2021;Shao and Yang, 2021), model analysis (Sun et al, 2019;Wang X. et al, 2022), and statistical analysis (Rizzo et al, 2020;Deng et al, 2022). Dai and Wang (2020) studied the influence of climate factors and land use factors on water yield using the geographic detector model and reported that precipitation and evapotranspiration were the primary driving factors in the Hengduan Mountain region.…”
Section: Introductionmentioning
confidence: 99%